2002
DOI: 10.1084/jem.20020642
|View full text |Cite
|
Sign up to set email alerts
|

Human CD4+CD25+ Regulatory, Contact-dependent T Cells Induce Interleukin 10–producing, Contact-independent Type 1-like Regulatory T Cells

Abstract: It has been recently demonstrated that regulatory CD4+CD25+ CD45RO+ T cells are present in the peripheral blood of healthy adults and exert regulatory function similar to their rodent counterparts. It remains difficult to understand how the small fraction of these T cells that regulate via direct cell-to-cell contact and not via secretion of immunosuppressive cytokines could mediate strong immune suppression. Here we show that human CD4+CD25+ T cells induce long-lasting anergy and production of interleukin (IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
319
5
12

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(359 citation statements)
references
References 31 publications
22
319
5
12
Order By: Relevance
“…Mice deficient in IL-10 develop severe inflammatory bowel disease [31][32][33] and IL-10 is important in oral tolerance development [34][35][36]. Noteworthy from this view is that GF animals are less prone to oral tolerization [37][38][39][40][41], and CD4 + CD25 + cells transferred from gnotobiotic mice show only an intermediate protection in a colitis model induced by the transfer of naive T cells depleted of regulatory cells [42].…”
Section: Discussionmentioning
confidence: 99%
“…Mice deficient in IL-10 develop severe inflammatory bowel disease [31][32][33] and IL-10 is important in oral tolerance development [34][35][36]. Noteworthy from this view is that GF animals are less prone to oral tolerization [37][38][39][40][41], and CD4 + CD25 + cells transferred from gnotobiotic mice show only an intermediate protection in a colitis model induced by the transfer of naive T cells depleted of regulatory cells [42].…”
Section: Discussionmentioning
confidence: 99%
“…These observations indicated that T regs play important roles in immunological homeostasis. Although the mechanisms of suppression by T regs are still unclear, it has been reported that T regs can inhibit the function of effector T cells directly through cell-to-cell contact or indirectly via the secretion of immune-suppressive cytokines, and also suppress the Agpresenting function of dendritic or NK cells (Dieckmann et al, 2002;Misra et al, 2004;Earle et al, 2005;Longhi et al, 2006;Smyth et al, 2006).…”
mentioning
confidence: 99%
“…The acquisition of antigen-specific regulatory functions by CD25 -T cells in tolerant animals could reveal an education [44,45] of conventional alloreactive CD25 -T cells by "natural" regulatory CD25 + T cells [37,38]. This hypothesis has to be reconciled with the apparent absence of expansion of the regulatory CD25 + T cell pool in tolerant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…In mice and rats, regulatory CD25 + T cells have been shown to control host anti-graft responses in recipients tolerant to skin allografts following multiple pretransplant donor-specific transfusions [20,27]. CD25 - The acquisition of antigen-specific regulatory functions by CD25 -T cells in tolerant animals could reveal an education [44,45] of conventional alloreactive CD25 -T cells by "natural" regulatory CD25 + T cells [37,38]. This hypothesis has to be reconciled with the apparent absence of expansion of the regulatory CD25 + T cell pool in tolerant recipients.…”
mentioning
confidence: 99%